2018
DOI: 10.1177/0961203318787058
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic nutritional index is correlated with disease activity in patients with systemic lupus erythematosus

Abstract: The prognostic nutritional index (PNI), which is calculated using serum albumin level and total lymphocyte count in the peripheral blood, is regarded as an index that reflects the immunonutritional status of patients. PNI was calculated in 217 systemic lupus erythematosus (SLE) patients according to the following formula: 10 × serum albumin value (g/dL) + 0.005 × peripheral lymphocyte count (/mm). Pearson's correlation analysis was used to elucidate the correlation between continuous variables. Linear and logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 29 publications
4
13
0
Order By: Relevance
“…As far as we are aware, only one study has investigated the association of PNI with disease activity in SLE [27]. Our findings agree with those reported by Ahn et al, where PNI was an independent predictor of active SLE in a population of Korean patients [27]. Thus, the present study considered together with previous work suggests that PNI may be a useful index for the evaluation of disease activity in lupus patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As far as we are aware, only one study has investigated the association of PNI with disease activity in SLE [27]. Our findings agree with those reported by Ahn et al, where PNI was an independent predictor of active SLE in a population of Korean patients [27]. Thus, the present study considered together with previous work suggests that PNI may be a useful index for the evaluation of disease activity in lupus patients.…”
Section: Discussionsupporting
confidence: 92%
“…NRI, developed at first for assessing patients with total parenteral nutrition, was found to be a sensitive and specific predictor for identifying patients with a risk of complications after surgery [18] and later adapted and validated in the geriatric population [19]. Interestingly, Ahn et al [27] recently showed that PNI correlated with SLE disease activity, claiming that PNI may provide an effective estimation of SLE activity. However, to the best of our knowledge, there have been no studies into the significance of other immune-nutritional indexes, including the CONUT score and NRI, in terms of predicting disease activity and damage accrual in SLE patients.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, lymphopenia has been included as a hematologic criterion according to the 1997 ACR and 2012 SLE International Collaborating Clinics SLE criteria [15,30] and has been reported to be associated with SLE disease activity and prognosis [31]. Similar findings were found in previous studies in which PNI was significantly correlated with SLE disease activity independent of other factors, supporting the results of our study [32,33].…”
Section: Discussionsupporting
confidence: 91%
“…However, a growing amount of evidence also suggests that PNI is associated with the prognosis of patients with non‐operable malignancies and chronic diseases . Furthermore, in a previous study, we have demonstrated that PNI is associated with disease activity in patients with systemic lupus erythematosus, which is a prototypical autoimmune disease . In the present study, to the best of our knowledge, we have first evaluated the clinical significance of PNI in patients with AAV.…”
Section: Discussionmentioning
confidence: 84%